A survey of some Chinese temples in Kuala Lumpur / Yap Beng Choo - Yap, Beng Choo (1984)
This study, which is a survey of some Chinese temples in Kuala Lumpur, is divided into six chapter. In Chapter One, the writer gives the aim of the study, ie.to gain an insight into some of the sociological aspects of the temples in Kuala Lumpur, the methods used and the problems faced in her study. Chapter Two is a review of the literature available on the Chinese religious systems and temples. Chapter Three is based upon the data collected on the Chinese temples in Kuala Lumpur, ie. on the establishment and the development of these temples, how they were set up and who set up these temples , the different types of temples and the descriptions of these temples. Chapter Four is on the social organization of the temples, ie. The people directly and indirectly involved in the running of the temples. Chapter Five gives a detailed description of the religious and social activities in the temples. In Chapter Six, the writer concludes on the significance of the Chinese temples to the Chinese in Malaysia today.